Single or Menu Contracting: An application of the Hersanyi Model to Mudaraba Financing - EL Fakir, Adil; Tkiouat, Mohamed (International Journal of Economics and Financial Issues, 2016)
In Islamic banking, the offering of a Mudaraba contract to a privately informed agent results in adverse selection. In incentive theory, a hypothesis is that the seller, in our case the Islamic bank, may offer different menu of contracts to separate non-efficient agents from the efficient ones. To test this hypothesis, we apply a game theory approach using an incomplete information model combined with an adverse selection index. From a rational point of view a bank would like to offer a higher type contract to an efficient agent to get higher rewards. Under an asymmetric case, however, we found evidence that in some cases offering a lower type contract can result in higher social value. Menu offering is found not to be the ultimate solution for agent’s types’ separation. Keywords: Mudaraba, Self-Selection Mechanism, Adverse Selection index, frequency of due diligence, Islamic venture capitalist (IVC), incomplete information. JEL Classifications: C7; G02; G24; G17